2023
DOI: 10.12681/npse.32592
|View full text |Cite
|
Sign up to set email alerts
|

Sociological Perspectives of Migrant Health Disparities and Access to Healthcare Services during and beyond the COVID-19 Pandemic: Voices of Immigrant and Refugee Women in Greece

Abstract: As the COVID-19 pandemic, as grew into a global health crisis, it created perilous and uncertain situations for vulnerable groups such as migrants, asylum seekers and refugees in the context of measures restricting mobility, social, economic, and educational life. This article, using the fields Sociology of Migration and Sociology of Health, focuses on female immigrants and refugees and their health and access to healthcare services in Greece. According to the results of in-depth interviews, based on the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The study by Guadagno (2020) explains the helplessness of migrant workers to cope with the health crisis due to inadequate access to basic healthcare facilities and financial instability, rendering them the most vulnerable sections and necessitating immediate attention from the concerned authorities. Likewise, Fouskas (2023) has revealed that protracted health‐related issues and insufficient healthcare services for female immigrants in Greece pose a menace to their job security. Assessing whether the pandemic aggravated the vulnerabilities among women more than men, Rukmini (2020) indicates the widening gender gap as an estimated 40% of women in India lost their jobs during the lockdown.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
“…The study by Guadagno (2020) explains the helplessness of migrant workers to cope with the health crisis due to inadequate access to basic healthcare facilities and financial instability, rendering them the most vulnerable sections and necessitating immediate attention from the concerned authorities. Likewise, Fouskas (2023) has revealed that protracted health‐related issues and insufficient healthcare services for female immigrants in Greece pose a menace to their job security. Assessing whether the pandemic aggravated the vulnerabilities among women more than men, Rukmini (2020) indicates the widening gender gap as an estimated 40% of women in India lost their jobs during the lockdown.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%